A DISCUSSION META-ANALYTICAL PERFORMANCE IN MATHEMATICS FOR SECONDARY EDUCATION BASED ON THE RESULTS OF CURRENT SARESP - Bassetto, Camila Fernanda [UNESP]; Lemes, Sebastiao de Souza [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
The objective of this work is to perform a meta-analysis of the current results of SARESP, considering the math proficiency of students in 3rd year high school of public schools. This meta-analysis revealed mismatches in the educational system as a whole in the various involved segments, directly or indirectly, which contribute to the teaching-learning process of the individual. Comparing the current results of SARESP was possible to observe the great deficiency presented by the students of 3rd year high school in solving mathematical problems involving simple concepts, sorting them at levels below the adequate when compared with the expected performance level to the series that they are. Based on this fact, which is unacceptable, we concluded that there is an immediate need to seek for explanation and overcoming ways for this situation. Otherwise, Brazilian education level will remain below of the basic.
Keywords: SARESP; High school; Math proficiency; Meta-analysis